Chamunda - Temples of India Project Team (Jio Institute, 2024)
An eight-armed Goddess stands on a lotus and naravahana (human corpse). Her form appears emaciated with sagging breasts and a sunken stomach. She has her mouth open and is pointing her little finger towards it with her left hand. She holds a trident in her right hand and a khappar (skull bowl) and naramunda (severed head) spear in the left hand. The remaining hands are broken. To her right, a lion-headed female (perhaps Narasimhi) and gana (attendant) is depicted, while on her left, a dog is seen licking the blood off the naramunda. A beaded halo is present behind her head. The gana and the naravahana exchange looks, with the gana holding his foot.